Learning Management In Modern Islamic Boarding School: A Study At Ar-Raudhatul Hasanah Islamic Boarding School, Medan - Ahmad Fauzi Ilyas; Mangunsong, Irvan; Mahmud Jailani Dalimunthe; Ahmad Faisal (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study aims to analyze learning management at Pondok Pesantren Ar-Raudhatul Hasanah as a modern Islamic boarding school integrating traditional Islamic values with contemporary educational management. This research employed a descriptive qualitative approach. Data were collected through interviews, participant observation, and document analysis involving educational administrators, teachers, dormitory supervisors, and students. Data analysis used the interactive model of Miles, Huberman, and Saldana. The findings reveal that learning management at the pesantren is implemented systematically, structurally, and holistically through integrated planning, implementation, supervision, and evaluation within a 24-hour boarding education system. Learning activities are coordinated institutionally and aligned with pesantren values. The study also shows that pesantren culture contributes significantly to students’ character formation through discipline, habituation, communal life, and continuous supervision. In addition, technology is utilized selectively as a supporting medium for learning and educational administration. The study concludes that learning management in modern pesantren is oriented not only toward academic achievement but also toward character development through the integration of educational systems and pesantren culture.